Achieving political rights, enhancing forest livelihoods: Latin American Indigenous and Afrodescendant women's views - Bolaños Cárdenas, O.; Monterroso, I. (Routledge, 2022)
This chapter discusses sociocultural and political processes constraining Indigenous and Afrodescendant women’s community forestry engagement, and how this influences their decision-making and benefit-sharing participation. Based on multi-stakeholder platform discussions by Latin American Indigenous and Afrodescendant women, it focuses on systemic and structural constraints on their visibility and effectiveness as peer political rightsholders. It presents the factors required to advocate for secure women’s rights in collective tenure systems and community forestry initiatives. These highlight the need to broaden the definition of community forestry to ensure women’s recognition as legitimate stakeholders, and their role in ethno-territorial livelihood strategies and knowledges.